2019
DOI: 10.1038/s41598-019-50916-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties and regenerative potential of Sr2+ and Ce3+ doped fluorapatites; a potential solution for peri-implantitis

Abstract: Scaffolds and implants in orthopaedics and regenerative dentistry usually fail because of bacterial infections. A promising solution would be the development of biomaterials with both significant regenerative potential and enhanced antibacterial activity. Working towards this direction, fluorapatite was synthesised and doped with Sr2+ and Ce3+ ions in order to tailor its properties. After experiments with four common bacteria (i.e. E. Coli, S. Aureus, B. Subtilis, B. Cereus), it was found that the undoped and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…The results have shown that both undoped and Ce 3+ -doped fluorapatites present better antibacterial effect than the Sr 2+ -doped ones. Importantly, high osteoconductivity leading to the differentiation of the dental pulp stem cells into osteoblasts was detected in Ce 3+ -and Sr 2+ -doped fluorapatites (Anastasiou et al, 2019).…”
Section: Cerium and Cerium Oxide Doping Into Grafting Scaffoldmentioning
confidence: 95%
See 1 more Smart Citation
“…The results have shown that both undoped and Ce 3+ -doped fluorapatites present better antibacterial effect than the Sr 2+ -doped ones. Importantly, high osteoconductivity leading to the differentiation of the dental pulp stem cells into osteoblasts was detected in Ce 3+ -and Sr 2+ -doped fluorapatites (Anastasiou et al, 2019).…”
Section: Cerium and Cerium Oxide Doping Into Grafting Scaffoldmentioning
confidence: 95%
“…However, it was found that CeO 2 NPs at low concentrations (1 mg/L) could not destroy the bacterial biofilms (Hou et al, 2015). Therefore, various cerium-and cerium oxide-based nanomaterials including doping metal ions (Atif et al, 2019), antibacterial element Au/Ag decorations (Babu et al, 2014;Wang et al, 2014), nanocontainers (Gagnon et al, 2015), dopants (Bomila et al, 2018), and a component of blend (Pandey et al, 2018a) were developed to optimize antimicrobial performance as well as physical and biological properties (Anastasiou et al, 2019;Bharathi and Stalin, 2019;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the composite with calcium fluoride nanoparticles would enhance remineralization and form fluorapatite that is able to resist future acidic challenges. Several studies have demonstrated the ability of forming fluorapatite using nanotechnology [ 15 , 16 ]. In one study, they manufactured fluorapatite nanoparticles and examined its doping with silver ion nanoparticles and evaluated its physical and antimicrobial effects.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, fluorapatite was incorporated into chitosan scaffolds. Fluorapatite maintained its structure, granted antimicrobial effects, and showed osteoconductive capability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This downside prompts the danger of bacterial adherence to implants covered with pristine HA ( Arcos and Vallet-Regí, 2020 ). Normally happening to follow components in bones (Magnesium, Zinc, Manganese, Strontium, Ag, Cerium, Copper) could be utilized as doping in HA to forestall microbial infections ( Arcos and Vallet-Regí, 2020 , Anastasiou et al, 2019 ). Zn is one of the significant follows components present in normal bone.…”
Section: Introductionmentioning
confidence: 99%